2021
DOI: 10.3389/fpls.2021.707061
|View full text |Cite
|
Sign up to set email alerts
|

Biochar, Compost, and Biochar–Compost Blend Applications Modulate Growth, Photosynthesis, Osmolytes, and Antioxidant System of Medicinal Plant Alpinia zerumbet

Abstract: Alpinia zerumbet (Zingiberaceae) is a unique ornamental and medicinal plant primarily used in food ingredients and traditional medicine. While organic amendments such as biochar (BC) and compost (Co) have been demonstrated to improve plant productivity, no studies have examined their effects on the growth, physiology, and secondary metabolites of A. zerumbet. This study evaluated the impact of the amendment of BC, Co, or a biochar and compost mixture (BC+Co) on modifying and improving the growth, photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Biochar has a multifunctional role, including GHG sequestration, improving soil properties, seed germination, crop yield and quality of horticulture produce, and increasing crop tolerance to abiotic and biotic stresses ( Kochanek et al., 2016 ; Almaroai and Eissa, 2020 ; Zulfiqar et al., 2021a ; Zulfiqar et al., 2021b ; Ibrahim et al., 2022 ; Ji et al., 2022 ; Taqdees et al., 2022 ) ( Figure 2 ). This review summarizes current progress on using BC to improve soil and substrate properties, seed germination, root growth, water and nutrient absorption, photosynthesis, crop yield, and tolerance to plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar has a multifunctional role, including GHG sequestration, improving soil properties, seed germination, crop yield and quality of horticulture produce, and increasing crop tolerance to abiotic and biotic stresses ( Kochanek et al., 2016 ; Almaroai and Eissa, 2020 ; Zulfiqar et al., 2021a ; Zulfiqar et al., 2021b ; Ibrahim et al., 2022 ; Ji et al., 2022 ; Taqdees et al., 2022 ) ( Figure 2 ). This review summarizes current progress on using BC to improve soil and substrate properties, seed germination, root growth, water and nutrient absorption, photosynthesis, crop yield, and tolerance to plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, both nitrogen and biochar increased leaf mass, stem mass, and root mass ( Supplementary Figure 1 ), indicating that nitrogen and biochar’s effects on root-shoot ratio might have been offset by their effects on aboveground biomass and underground biomass. Recent studies have shown that net photosynthesis rate ( P n ) and transpiration rate ( T r ) increased by 19 and 40% in the biochar treatments, respectively, compared to control ( Zulfiqar et al, 2021 ). Biochar significantly increased net photosynthetic rate, transpiration rate, stomatal conductance, and water use efficiency during the plant growth period, relative to control ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the branches and leaves of ginger contain volatile oils, phenols, pyrones, flavonoids, diterpenes, and other compounds with strong antibacterial effects [7,8]. Therefore, there is a need to construct a bacterial agent that can quickly detoxify the branches and leaves of Yanshan ginger for efficient fermentation and production of bio-organic fertilizer [9,10].…”
Section: Introductionmentioning
confidence: 99%